The quasi-liquid layer thickness controls clathrate hydrates’ growth rate - Xinrui Cai; Matteo Salvalaglio; Alberto Striolo (Proceedings of the National Academy of Sciences, 2026)
Clathrate hydrates are fascinating materials that offer many attractive benefits for carbon sequestration, water desalination, intermittent natural gas storage, chemical separations, and other applications. However, their slow growth kinetics prevents the cost-effective realization of hydrate-based technologies. To overcome this challenge, chemical additives have been identified to control hydrates’ growth rate. Among others, the surfactant sodium dodecyl sulfate (SDS) and the amino acid L-tryptophan (TRP) are both effective at low concentrations. While SDS is widely available but raises environmental concerns, TRP is environmentally benign. Although both SDS and TRP are interfacially active, the molecular mechanism responsible for their ability to enhance hydrate growth is not known, nor is the reason why these compounds are effective at low concentrations. It is demonstrated here that both SDS and TRP, when adsorbed, affect the thickness of the quasi-liquid layer (QLL) at the hydrate–water interface, which, in turn, promotes the adsorption of CO 2 from the liquid phase to the growing hydrate. The QLL amplifies the effect to mesoscopic length scales, explaining why small amounts of these surface-active compounds enhance hydrate growth rate.